Acute myocardial infarction in sub-Saharan Africa: the need for data. - Julian T Hertz; Joseph M Reardon; Clarissa G Rodrigues; Luciano de Andrade; Alexander T Limkakeng; Gerald S Bloomfield; Catherine A Lynch (PLoS ONE)
Background Trends in the prevalence of acute myocardial infarction in sub-Saharan Africa have not been well described, despite growing recognition of the increasing burden of cardiovascular disease in low- and middle-income countries. The aim of this systematic review was to describe the prevalence of acute myocardial infarction in sub-Saharan Africa. Methods We searched PubMed, EMBASE, Global Health Archive, CINAHL, and Web of Science, and conducted reference and citation analyses. Inclusion criteria were: observational studies, studies that reported incidence or prevalence of acute myocardial infarction, studies conducted in sub-Saharan Africa, and studies that defined acute myocardial infarction by EKG changes or elevation of cardiac biomarkers. Studies conducted prior to 1992 were excluded. Two independent reviewers analyzed titles and abstracts, full-texts, and references and citations. These reviewers also performed quality assessment and data extraction. Quality assessment was conducted with a validated scale for observational studies. Findings Of 2292 records retrieved, seven studies met all inclusion criteria. These studies included a total of 92,378 participants from highly heterogeneous study populations in five different countries. Methodological quality assessment demonstrated scores ranging from 3 to 7 points (on an 8-point scale). Prevalence of acute myocardial infarction ranged from 0.1 to 10.4% among the included studies. Interpretation There is insufficient population-based data describing the prevalence of acute myocardial infarction in sub-Saharan Africa. Well-designed registries and surveillance studies that capture the broad and diverse population with acute myocardial infarction in sub-Saharan Africa using common diagnostic criteria are critical in order to guide prevention and treatment strategies. Registration Registered in International Prospective Register of Systematic Reviews (PROSPERO) Database #CRD42012003161.